Investigation on the strategy and impact of artificial insemination programme and performance of Crossbred Cattle in Bangladesh - Majid, M.A.; Nahar, T. N.; Hossain, K. M.; Talukder, A. I. (BRAC Research and Evaluation Division (RED), 2019)
This collaborative study was -sponsored by BRAC and executed by the Bangladesh Livestock Research Institute (BLRI), Savar with logistic and other support of the Department ofUvestock Services (DLS), GOB to investigate the strategy and effectiveness of the artificial insemination (AI) programme of the DLS and BRAC at different AI centres, sub-centres and points and to evaluate the performance of the crossbred cattle in Bangladesh. Four district AI centres, 12 AI sub-centres, 16 AI points under DLS and 7 AI points under BRAC were selected. Three villages with varying distance from Al centres or sub-centres of each district and two villages under each Al point were selected. Twelve households rearing crossbred cattle from each village were selected to study the performance of crossbred cattle while 25 households were selected from each village to determine their socioeconomic status and the impact of Al. Findings show the Al bulls supplied to district AI centres did not strictly conform to the national breeding policy. The semen evaluation system was satisfactory at the central AI laboratory but were not so at different district AI laboratories. Semen preservation systems and facilities were also not very scientific. Almost 50% of the study areas were supplied with liquid semen in vials and the supply was often irregular. The mode of transportation was also traditional which included bus, rickshaw, bicycle or even walking. Most of the AI sub-centres could not examine semen due to absence of equipment and facilities such as microscope, electricity or due to some social problem. Milk yields of crossbred cattle varied and was found higher during the rainy season in Jessore, Rangpur and Comilla but were lower in flood prone areas in Tangail. The best performance was found among Local x Friesian cows followed by Local x Sindhi and L x J. The reproductive performances of Friesian cross progenies were found better than others. Data showed that BRAC cattle rearers had smaller cultivated land, higher level of education, higher involvement of women in livestock rearing and greater awareness about AI services than non-BRAC rearers. Almost 100% of BRAC rearers used AI to cross their cattle. They also took better care of their animals and achieved higher conception rate.